2004
DOI: 10.1111/j.1600-0692.2004.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of submerged arc weld‐metal composition from flux ingredients with the help of statistical design of mixture experiment

Abstract: A prediction model has been developed for submerged arc weld-metal chemical composition in terms of flux ingredients with the help of statistical experiments for mixture (extreme vertices design). Bead-on-plate weld deposits as per statistical mixture design experiments were performed at the following welding parameters: current (400 A), voltage (26 V), speed (4.65 mm/s) and electrode extension (30 mm) using CaO-MgO-CaF 2 -Al 2 O 3 flux system. The results show that some of the individual flux ingredients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
61
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 16 publications
(34 reference statements)
0
61
0
Order By: Relevance
“…The quality of weld-metal is often evaluated by many characteristics such as chemical composition, mechanical properties, bead profile and microstructure. Studies have shown that these characteristics are influenced by the welding flux formulation; therefore it is important to select the right type of welding flux ingredients and choose the appropriate proportions of the various flux ingredients to attain a good weld-metal quality [2][3][4][5][6][7][8][9][10] . The conventional approach to welding flux development is by experimental optimization.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The quality of weld-metal is often evaluated by many characteristics such as chemical composition, mechanical properties, bead profile and microstructure. Studies have shown that these characteristics are influenced by the welding flux formulation; therefore it is important to select the right type of welding flux ingredients and choose the appropriate proportions of the various flux ingredients to attain a good weld-metal quality [2][3][4][5][6][7][8][9][10] . The conventional approach to welding flux development is by experimental optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The XVERTD method is a proven approach that is sufficient not only to fit the proposed model but also allows a test of model adequacy from a minimal experimental efforts 14 . Kanjilal and his co-investigators [5][6][7][8] used their experimental data to develop prediction models for the measured responses such as weld-metal composition, mechanical properties, microstructure and element transfer characteristics of the flux. However, they did not use the models to perform optimization on the responses.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations